2015
DOI: 10.15171/joddd.2015.046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Serum Lipid Profile andOral Lichen Planus

Abstract: Background and aims. Oral lichen planus (OLP) is an immunologic disorder. A large number of studies have reported that lipid rafts have a key role in receptor signaling of lymphocytes. Here, we explore the potential of lipid rafts as targets for the development of a new class of agents to down-modulate immune responses and treat autoimmune diseases.Materials and methods. The present cross-sectional study evaluated 88 patients referring to the Department of Oral Medicine in 3 groups (Group 1: erosive OLP; Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…When compared to the control group they found a significant relation between oral LP with triglycerides levels and low HDLC levels (p value of 0.00 and 0.02 respectively). 19 Study done by Sarkar et al could also demonstrate similar results in a case control study done among 25 LP patients and age and gender matched controls. Along with altered HDLC and triglyceride levels, they found that the levels of LDL was also high among LP patients.…”
Section: Serum Lipidssupporting
confidence: 64%
See 1 more Smart Citation
“…When compared to the control group they found a significant relation between oral LP with triglycerides levels and low HDLC levels (p value of 0.00 and 0.02 respectively). 19 Study done by Sarkar et al could also demonstrate similar results in a case control study done among 25 LP patients and age and gender matched controls. Along with altered HDLC and triglyceride levels, they found that the levels of LDL was also high among LP patients.…”
Section: Serum Lipidssupporting
confidence: 64%
“…18 Similarly by Mehdipour in their study reported increased prevalence of LP among patients of age group 40 to 60 yrs. 19 Among the patients with metabolic syndrome, maximum number of LP patients belonged to the sixth decade which was 7 (38.88%) of the 18 patients. While among the control group, maximum individuals with metabolic syndrome belonged to fifth and sixth decade which was 9 (28.12%) each in both decades.…”
Section: Agementioning
confidence: 97%
“…Several studies were done by Mehdipour et al . [ 11 ] and Ebrahimi et al . [ 12 ] show variable results in OLP and control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Besides Candida albicans , Non- C. albicans strains, such as Candida parapsilosis , Candida tropicalis , C. dubliniensis , Candida krusei and Candida glabrata , are frequently detected in OLP and OLL. [ 6 7 8 9 10 11 12 13 ] Various studies are done which have shown that there is a differing capability of various strains to promote dysplasia by catalyzing the production of nitrosamine (carcinogenic) and also because of metabolism of ethanol to the carcinogenic acetaldehyde and induction of proinflammatory cytokines. [ 14 ] As there is a differing pathogenic potential of various Candida species, identification of species may play a pivotal role in successful clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…The final consequence is an increased accumulation of cholesterol in cells. [ 10 ] When the compensatory response (inflammation) is not able to repair injury, it turns into a harmful reaction, and the lipid changes will become chronic, either by repeated or overwhelming stimulus, enhancing the formation of atherosclerotic lesions. Thus, the classical lipid changes associated may be envisioned as a highly conserved evolutionary response aimed at tissue repair.…”
Section: Discussionmentioning
confidence: 99%